Extended-spectrum β-lactamase and carbapenemase-producing Enterobacterales among adult patients and their family members at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia - Dessie Abera; Adane Mihret; Surafel Fentaw; Eyob Beyene; Abel Abera Negash; Woldaregay Erku Abegaz (PLoS ONE, 2026)
Background Extended-spectrum β-Lactamase and Carbapenemase-producing Enterobacterales cause severe infections and currently, they are spreading beyond hospitals and becoming a serious global health concern. They often colonize the gut silently, facilitating the transmission of resistant bacteria between patients and family members. Objective We sought investigate the prevalence and molecular characteristics of Extended-spectrum β-Lactamases-producing Enterobacterales (ESBL-PE), Carbapenem-resistant Enterobacterales (CRE), and factors associated there in among admitted adult patients and their family members at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia. Methods A case-control study was conducted among 100 patients and their respective 100 family members from February 2023 to October 2023. Stool specimens were collected and processed using standard microbiological techniques. Antimicrobial susceptibility testing and ESBL production were determined using VITEK 2 system. Carbapenemase production was tested using modified carbapenem Inactivation method, and detection of resistance genes was performed by PCR. Result Intestinal colonization with ESBL-PE was higher in patients (39.0%) than their respective family members (24.0%) (P = 0.028). Among patients, ESBL production was common in E. coli , 40.3% and K. pneumoniae, 34.7% than their family members 24.2% and 22.2%, respectively. Of the ESBL-PE isolates, 84.6% from patients and 100% from family members carried at least one ESBL encoding gene, with bla CTX-M being the predominant. Colonization with CRE and Carbapenemase-Producing Carbapenem-Resistant Enterobacterales was found to be 19.0% and 10.0%, respectively. These were identified only among patients, with bla NDM and bla OXA-48 are the most prevalent genes. Older age (>53 years) (P = 0.02) and previous ICU admission (P < 0.001) showed significant association with ESBL-PE colonization. Conclusion ESBL-PE colonization was more prevalent in patients compared to their family members, with bla CTX-M identified as the most common gene. Exclusive detection of carbapenemase genes among patients, and the association of previous ICU admission with ESBL-PE colonization, highlights the need for targeted screening and strengthened infection prevention.